Chirality Matters: Biological Activity of Optically Pure Silybin and Its Congeners - Křen, Vladimír (International journal of molecular sciences, 2021)
This review focuses on the specific biological effects of optically pure silymarin flavo-nolignans, mainly silybins A and B, isosilybins A and B, silychristins A and B, and their 2,3-dehydro derivatives. The chirality of these flavonolignans is also discussed in terms of their analysis, preparative separation and chemical reactions. We demonstrated the specific activities of the respective diastereomers of flavonolignans and also the enantiomers of their 2,3-dehydro derivatives in the 3D anisotropic systems typically represented by biological systems. In vivo, silymarin flavonolignans do not act as redox antioxidants, but they play a role as specific ligands of biological targets, according to the "lock-and-key" concept. Estrogenic, antidiabetic, anticancer, antiviral, and antiparasitic effects have been demonstrated in optically pure flavonolignans. Potential application of pure flavonolignans has also been shown in cardiovascular and neurological diseases. Inhibition of drug-metabolizing enzymes and modulation of multidrug resistance activity by these compounds are discussed in detail. The future of "silymarin applications" lies in the use of optically pure components that can be applied directly or used as valuable lead structures, and in the exploration of their true molecular effects.
Keywords: silibinin; Animals; fytogenní protinádorové látky; Antineoplastic Agents, Phytogenic; lidé; Antioxidants; antiinfekční látky; zvířata; Silybin; Anti-Infective Agents; Stereoisomerism; stereoizomerie; antioxidancia; Humans